2019
DOI: 10.5219/978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and genetic diversity in some Egyptian wheat (Triticum aestivum L.) using microsatellite markers

Abstract: <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…al., (2016);ŽIAROVSKÁ et. al., (2017); ANSARI et al, (2018); EL-FIKI et al, (2019); ŠTIASNA et al, (2019). The present study is focused on estimation of genetic distance between 56 Tunisian castor genotypes, based on 20 SSR markers.…”
Section: Introductionmentioning
confidence: 96%
“…al., (2016);ŽIAROVSKÁ et. al., (2017); ANSARI et al, (2018); EL-FIKI et al, (2019); ŠTIASNA et al, (2019). The present study is focused on estimation of genetic distance between 56 Tunisian castor genotypes, based on 20 SSR markers.…”
Section: Introductionmentioning
confidence: 96%
“…They are abundant and scattered all over the eukaryotic genomes with a high polymorphism rate (Kesawat and Kumar, 2009). Different studies have reported the use of SSRs to reveal polymorphisms in the wheat population (Khan et al 2015;Zarei., et al, 2016;Ya Narantsetseg et al, 2017;Salehi et al 2018;Yadav and Chand, 2018;El-Fiki and Adly, 2019). The results of these investigations indicated that wheat populations had high genetic diversity that can be used in wheat conservation and breeding programs, as well most SSR markers used showed a high level of polymorphism in wheat.…”
Section: Introductionmentioning
confidence: 97%